Ionic Liquids in Catalysis - Maciejewski, Hieronim (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Due to their distinctive properties, ionic liquids have attracted the great and unflagging interest of researchers for over 30 years. This interest has been focused mainly on their use as a green alternative to volatile organic solvents. However, they often act not only as solvents but also as catalysts, catalyst immobilizers and initiators. Over 100 types of chemical reactions are known in which ionic liquids (ILs) were applied successfully. This Special Issue is aimed at showing the most recent advances and trends in the design, synthesis and characterization of catalysts based on ILs, as well as presenting their activity and application potential.